Pengaruh Literasi Keuangan terhadap Kinerja UMKM se-Eks Karesidenan Besuki Jawa Timur - Aryo Prakoso (Valid: Jurnal Ilmiah, 2020)
Most of the micro, small, and medium enterprises (MSMEs) still need difficulties to grow, develop, and be consistent in doing business. Important information about finance, market dynamics, competitors, and management of governance is still prevalent in the MSME level. The fundamental problem is the low management ability in managing information and processing financial data. SMEs who are less aware of corporate governance and business management. Efforts to enrich the knowledge of financial management through financial literacy. Strategic initiatives in the management and sustainability of MSMEs can be through the education of businesses towards the level of expertise and ability to receive commercial information so that that management will develop. The object of this research is MSMEs in the coastal areas Eks-Besuki Karesident, of Jember, Bayuwangi, and Situbondo. This research uses quantitative methods, exogenous variables which are used are financial literacy with financial indicators, investment, savings, conversely endogenous variables are used to improve performance with indicators of quality, results, cost efficiency, and employee relations. Analysis using Structural Equation Modeling. The results obtained by financial literacy have a significant effect on the performance of MSMEs, the results of their assessment of the level of understanding of financial literacy at MSMEs in the former residence of Besuki can improve the performance of MSMEs